Meninjau Ulang Jinayat Aceh: Studi Komparatif Penegakan Hukum Pidana Islam dan Standar HAM Internasional - Muzakkir Muzakkir; Fouza Azwir Abdul Azis; Rizki Maulana (Al-Widad, 2024)
This study aims to re-examine the alignment and potential discrepancies between the Aceh Jinayat legal provisions and international human rights instruments such as the Universal Declaration of Human Rights (UDHR), the International Covenant on Civil and Political Rights (ICCPR), and the Convention Against Torture (CAT). This research employs a library research method with a qualitative approach and a normative-comparative analysis. The primary data in this study consist of the Aceh Jinayat Qanun and international human rights instruments (UDHR, ICCPR, and CAT), while secondary data include academic literature, scholarly journals, and relevant reports from human rights institutions. The findings indicate that there is a degree of compatibility between the Aceh Jinayat law and international human rights standards in terms of moral protection, social order, and the enforcement of public ethics. However, several provisions require strengthening and reformulation based on the principles of substantive justice, proportionality, and human rights protection.